Polarization functions of Pb-Sn-Cd alloys treated with sulfuric acid - Al-Khateeb, Ismail K.; Flaih, Hanan H.; Al-Marsomi, Sabri (2006)
The study is conducted to investigate the polarization functions of different lead alloys including impurities of 0.6-2% tin and 0.03-0.09% cadmium metals. Alloys were immersed in sulfuric acid with density of 1.20, 1.25, 1.30, and 1.40 g cm-3 at temperature of 298K. Highest corrosion rate occurred at 1.20 and 1.25 g cm-3 densities, while the density of 1.30 g cm-3 showed the lowest corrosion rate especially for alloys containing more than 0.6% Sn and 0.03% Cd. Polarization studies showed that corrosion current density was reduce by increasing acid density from 1.20 to 1.30 g cm-3 with positive elevation in corrosion potential. The evolution of hydrogen was the main cathodic reaction, as deduced from Tafel slopes and the corresponding transfer coefficients, while metal dissolution was the main anodic reaction. The values of polarization resistance, critical current density and passive current density were decreased in alloys of very low levels of impurities and increased with high levels of Sn and Cd.